GAMBARAN PENGGUNAAN ALAT PELINDUNG DIRI PEKERJA BONGKAR MUAT PETIKEMAS PT. X SURABAYA - Tofan Agung; Yudi A. (Journal of Industrial Hygiene and Occupational Health, 2016)
Loading and unloading containers activities at one of terminal has a high operating level compared with some other terminals in the Port of Tanjung Perak Surabaya Loading and unloading activities with high operational causes various risks, especially risks to the health and safety of workers. One way to prevent accidents is to use PPE (Personal Protective Equipment) is appropriate. This research aims to describe the used of PPE on loading and unloading workers, with the observational method. Based on observations to 20 employees, the results was that majority of workers used safety shoes. Mask is a type of personal protective equipment used by workers at least. Data recorded in the company's result showed that the risk of work accidents index were at 9.103. Based on data obtained during observations showed that 25% of workers were not using the appropriate PPE. Conclusion: various PPE has been provided by the company and the use of masks need to be improved.